Cognitive testing to evaluate revisions to the Vaccine Adverse Event Reporting System (VAERS) reporting form. Issue 18 (25th April 2017) - Suragh, Tiffany A.; Miller, Elaine R.; Hibbs, Beth F.; Winiecki, Scott K.; Zinderman, Craig; Shimabukuro, Tom T.
Abstract: Introduction: The Vaccine Adverse Event Reporting System (VAERS) is the spontaneous (passive) reporting system CDC and FDA use to monitor vaccine safety. We used cognitive testing to evaluate proposed revisions to the current VAERS form. Methods: We conducted in-person cognitive interviews with 22 volunteers to evaluate proposed revisions in a prototype VAERS 2.0 form (new VAERS form). We analyzed data using thematic analysis. Results: Repeating themes included preferences for: brevity, simplicity and clarity; features to minimize time requirements and facilitate ease of completion; logical ordering of questions by topic and importance; and visual cues like color-coded highlighting. Interviews identified instances of discordance between the intended meaning questions (from the perspective of CDC and FDA) and interpretation by volunteers. Conclusions: Cognitive testing yielded useful information to guide further revisions of the VAERS form. Cognitive testing can be an effective tool for public health programs interested in developing surveys and reporting forms.